The Legal Protection of Genetic Resources Associated with Traditional Knowledge in Indonesia: Juridical Implications of the GRATK Treaty - Yuliati Yuliati; Agung Sudjatmiko; Moh. Fahrial Amrulla (Universitas Muhammadiyah Bandung, 2026)
This study aims to analyze the legal consequences of Indonesia’s ratification of the GRATK agreement on the patent framework. As is known, the recognition and protection of Intellectual Property Rights (IPR) has undergone rapid development, especially communal IPR such as the protection of genetic resources and traditional knowledge, which demand fair and adequate legal protection for all parties. The emergence of unfair practices in the use, commercialization (biopiracy), and restriction of ownership of traditional knowledge through IPR instruments has created a conflict of interest between the owners of traditional knowledge and those who develop and commercialize it. This research focuses on the legal protection of traditional knowledge through the international agreement, the GRATK Treaty, which the Indonesian government has signed, and its legal consequences. This study uses normative legal research, analyzing Law No. 65 of 2024 concerning Patents and the 2024 GRATK Treaty as the main sources. The results of the study show that the GRATK agreement provides a fair framework for the recognition and legal protection of genetic resources, as desired by countries that own genetic resources in a world dominated by developing countries. However, the study also argues that while the GRATK Agreement and its incorporation into Indonesian patent law represent significant progress, their effective implementation requires comprehensive regulatory harmonization and the development of sui generis mechanisms to protect communal intellectual property, thereby safeguarding the national interest in genetic resources and traditional knowledge.